Change in Susceptibility Values in Knee Cartilage After Marathon Running Measured Using Quantitative Susceptibility Mapping. Issue 5 (24th May 2021) - Zhang, Ming; Li, Yufei; Feng, Ruimin; Wang, Zhongzheng; Wang, Wenjin; Zheng, Nan; Wang, Shaobai; Yan, Fuhua; Lu, Yong; Tsai, Tsung‐Yuan; Wei, Hongjiang
Abstract : Background: Quantitative susceptibility mapping (QSM) has been used to study the magnetic susceptibility properties of collagen fibers in articular cartilage; however, it is unclear whether QSM is sensitive to changes due to degradation caused by long‐distance running. It is clinically important to understand the link between long‐distance running and microstructural changes in knee cartilage. Purpose: To investigate the ability of QSM to assess microstructural changes within cartilage after repetitive loading. Study Type: Prospective. Population: Thirteen recreational, male long‐distance runners. Field Strength/Sequence: Three‐dimensional gradient recalled echo acquired at 3 T. Assessment: Magnetic resonance imaging (MRI) and 3D kinematics (translations and rotations during treadmill walking and running) of the knee joint were collected before and after marathon running. The compartments for analysis included the patella, trochlea, and subregions of femoral and tibial cartilage. Changes in regional susceptibility and cartilage thickness were calculated after marathon running. A susceptibility profile was obtained by fitting susceptibility as a function of the normalized depth of cartilage from the superficial to deep layers. Statistical Tests: Paired t ‐test or Wilcoxon signed‐rank test, 95% confidence interval (CI) of the depth‐wise susceptibility profile, Pearson correlation or Spearman correlation. Results: There was a statistically significant increase in susceptibility value in the weight‐bearing region of central medial femoral cartilage (cMF‐c) after marathon running (pre‐marathon: −0.0219 ± 0.0151 ppm, post‐marathon: −0.0070 ± 0.0213 ppm, P < 0.05), while the cartilage thickness did not show significant changes in any regions ( P ‐value range: 0.068–0.963). Significant susceptibility elevations occurred in the middle and deep layers of cMF‐c (95% CIs did not overlap). A trend toward a positive correlation was found between the changes in susceptibility value in cMF‐c and proximal–distal translation of the knee joint during walking ( r = 0.55, P = 0.101) and running ( r = 0.57, P = 0.089). Data Conclusion: Localized magnetic susceptibility alterations were observed within knee cartilage in the weight‐bearing area after repetitive loading without any morphologic changes. Level of Evidence: 2 Technical Efficacy: Stage 2